Occurrence of hypomagnesemia in children admitted to paediatric intensive care unit - R., Deekshitha; P., Shilpa; K. M., Chaitra (International Journal of Contemporary Pediatrics, 2023)
Background: To determine the occurrence of hypomagnesemia in children admitted to paediatric intensive care unit in tertiary care centre. Methods: It is a prospective chart review of 250 children aged 1 month to 17 years admitted in paediatric intensive care unit of Kempegowda Institute of Medical Sciences during 12 months from January 2022 to December 2022 and recorded serum Mg level on admission. Patients were divided into two groups according to their Mg level (Normo-magnesemic and Hypomagnesemic) and their p value, crude and adjusted odds ratios were calculated. Results: Upon admission in PICU 100 (40%) patients were found hypomagnesemia. There was no difference in age and gender between two groups. The important risk factors identified were age greater than 2 years (p=0.05, AOR 3.71), sepsis (p=0.03, AOR-3.11), hypokalemia (p=0.06, AOR-1.8), hypocalcemia (p=0.03, AOR-1.6), diuretic use (p=0.05, AOR-1.37), Aminoglycoside use (p=0.003, AOR-3.12), and hospitalization greater than 5 days (p=0.05, AOR-1.71). Those with normomagnesemic had higher mortality rate (32/100 or 32%) than those with hypomagnesemia (22/79 or 27.8%) Conclusions: The present finding indicates that hypomagnesemia is common among PICU patients.